1963
DOI: 10.1083/jcb.18.3.621
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscope Studies on Developing Crayfish Oocytes With Special Reference to the Origin of Yolk

Abstract: The endoplasmic reticulum is composed, in places, of stacks of parallel cisternae which are limited by membranes having great numbers of ribosomes attached to their outer surface. These are connected with other cisternae of similar structure but with fewer ribosomes and without preferred orientation. The latter extend in all directions from the stacked cisternae, branching and anastomosing freely so that the entire system of membrane-limited cisternae appears interconnected; a morphological condition suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
2

Year Published

1965
1965
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(44 citation statements)
references
References 29 publications
0
42
0
2
Order By: Relevance
“…This has also been observed in other decapods (King, 1948;Kessel, 1968). Raven (1961) and Beams and Kessel (1963) reported that the oocytes remove the material, or part of it, from these cells to form the yolk.…”
Section: Discussionmentioning
confidence: 75%
“…This has also been observed in other decapods (King, 1948;Kessel, 1968). Raven (1961) and Beams and Kessel (1963) reported that the oocytes remove the material, or part of it, from these cells to form the yolk.…”
Section: Discussionmentioning
confidence: 75%
“…The oogonia in P. clarkii [21,29], A. leptodactylus [23] and C. quadricarinatus [30] contain thread-like and granular basophilic chromatin material in their very large nuclei.This is very similar to that seen in H.gammarus. In addition, at proliferation stage in H. gammarus the differentiation of the chromatin material from a filamentous pattern towards a granular structure and the weak eosinophilic nature of the cytoplasm is similar to C. quadricarinatus [30].…”
Section: Ovarymentioning
confidence: 99%
“…The cytochemistry, and particularly the origin, of oocyte yolk inclusions have been thoroughly studied in several crustaceans using electron microscopy : the endogenous origin of the yolk protein in Orconectes (Beams and Kessel, 1963) and its endogenous and exogenous origin in Libinia emarginata (Hinsch and Cone, 1969), Orchestia gammarellus (Zerbib, 1973(Zerbib, , 1976 and Eriocheir sinensis (Dhainaut and De Leersnyder, 1976). Only one ultrastructural study by Rateau and Zerbib (1978) (1971), Cruickshank (1971), Favard-Sereno (1971) and Nardon (1978).…”
mentioning
confidence: 99%